MATHEMATICAL MODEL’S SYNTHESIS FOR INFORMATION SYSTEM OF ADIPOSITY DIAGNOSIS OBESITY IN - Высоцкая, Елена Владимировна; Порван, Андрей Павлович; Амбросов, Дмитрий Антонович; Доброродняя, Анна Сергеевна; Доброродняя, Ирина Сергеевна (Eastern-European Journal of Enterprise Technologies, 2012)
In this paper a diagnostic model for the derivation of the patients adiposity stages with arterial hypertension, resulting from discriminant analysis of clinical and laboratory research too is proposed.